A Collaborative Learning Proposal for Predict-Observe-Explain Model supported by Mobile Environment - Gagno Júnior, Fernando; Beltrame, Walber Antonio Ramos (Anais do Workshop on Advanced Virtual Environments and Education (WAVE); 2020: Anais do III Workshop on Advanced Virtual Environments and Education, 2021)
Virtual learning environments were designed to stimulate social competences, such as altruism, responsibility, communication, planning and coordination. It is observed that creation of technology for active methods, as for the Predict-Observe-Explain (POE) model. However, advances in the design of these environments are necessary to support aspects of collaboration and mobility. The goal of this article is to present a proposal for a mobile platform that organizes a workflow of revised POE models, based on debates. The methodology and expected results are presented.